THE EFFECTIVENESS OF COMMUNICATIVE LANGUAGE TEACHING IN DEVELOPING SPEAKING FLUENCY AMONG UNIVERSITY STUDENTS (International journal of artificial intelligence, 2025)
Communicative Language Teaching (CLT) is one of the most influential approaches in modern foreign language education, emphasizing meaningful interaction and real-life communication. This article investigates the effectiveness of CLT in developing speaking fluency among university students learning English as a foreign language. The study is based on a qualitative and descriptive analysis of theoretical literature and classroom practices. The findings reveal that CLT significantly improves learners’ speaking fluency, confidence, and communicative competence by creating authentic interaction, encouraging student participation, and reducing anxiety. The article also discusses challenges in implementing CLT at the university level and offers practical recommendations for English language teachers.